BENTO Curriculum Design for Eating Habits of Early Children - Dewi Mulyani; Dinar Nur Inten; Helmi Aziz (STAI Hubbulwathan Duri, 2024)
The BENTO (Bersih, Sehat, Halalan Thoyyiban) Curriculum was developed to instill early childhood eating habits that are clean, healthy, and halal, incorporating religious values into daily routines. This study assesses the curriculum’s development and effectiveness in promoting these values. The curriculum was designed and tested using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation phases. This structured approach allowed researchers to methodically develop and refine the curriculum based on its goals. The BENTO curriculum emphasizes a holistic, integrative approach, focusing on health, safety, and the meaningful incorporation of Islamic principles in early education. Through activities, children learn about the health and religious benefits of eating according to Islamic practices. Content areas include basic needs, animals, professions, plants, and culture, with learning resources drawn from children’s personal experiences, community environments, events, and designated learning times. The curriculum fosters moral education by teaching, internalizing, and adapting religious values in eating habits. It utilizes engaging and child-centered strategies to make the learning experience both enjoyable and meaningful, contributing to the development of moral awareness and actions in young children. The BENTO curriculum provides an effective framework for integrating religious and health-related values into early childhood eating habits. The authentic evaluation process highlights its potential for meaningful impact in early education. Further research should explore its applicability in diverse cultural contexts.